Autism spectrum disorder is associated with an increased risk of development of underweight in children and adolescents: A systematic review and meta-analysis. (June 2022) - Kahathuduwa, Chanaka N.; Dhanasekara, Chathurika S.; Wakefield, Sarah; Moustaid-Moussa, Naima; Mastergeorge, Ann
Abstract: Background & Aims: Multiple observational studies have examined the association between autism spectrum disorder (ASD) and underweight, yet the evidence remains ambiguous. We examined the pooled prevalence and relative risk of developing underweight among children with ASD in a systematic review and meta-analysis and examined the effects of potential risk factors in a meta-regression. Methods: ProQuest, PubMed, Scopus and Web of Science databases were systematically searched and screened per the PRISMA guidelines. DerSimonian–Laird random-effects meta-analyses were performed using the 'meta' package in R to determine the pooled prevalence and the relative risk of underweight among children with ASD. Meta-regression analyses examined the moderator effects of risk factors. Results: Underweight had a prevalence of 6.5% (95% CI, 5.1–8.2) among children with ASD overall (29 study groups). Children with ASD possessed a 28.5% (8 studies) greater risk of being underweight vs. neurotypical controls. Meta-regression analyses revealed that non-Caucasian origin and male sex may increase the risk of being underweight in children with ASD. Conclusions: Children with ASD seem to be at an increased risk of being underweight, which may further impair the clinical outcomes and quality of life. Clinicians need to vigilantly monitor weight and height among children with ASD to prevent underweight and associated complications. Future studies should aim to establish factors that may contribute to the development of underweight among children with ASD. Highlights: Association between autism spectrum disorders (ASD) and underweight was studied. Prevalence of underweight among children with ASD was 6.5% (95% CI, 5.1–8.2). Children with ASD had a 28.5% greater risk of being underweight.